Most of us have learned these facts many times. Use this quick drill to refresh your mind—knock off the dust.

*x*times*y*=*x*times*y*=*xy**x*(*y*) =*x*(*y*) =*xy**x***y*=*x***y*=*xy**x*·*y*=*x*·*y*=*xy**2x*(*y*) =*2x*(*y*) =*2xy**2x*(*3y*) =*2x*(*3y*) =*6xy**4x*(*3y*) =*4x*(*3y*) =*12xy**3x*(*6y*) =*3x*(*6y*) =*18xy**x*times*x**x*times*x*=*x*^{2}*x*(*x*) =*x*(*x*) =*x*^{2}*x*(*xy*) =*x*(*xy*) =*x*^{2}y*xy*(*y*) =*xy*(*y*) =*xy*^{2}*x*÷*y*=*x*÷*y*=^{x}/_{y}*y*÷*x*=*y*÷*x*=^{y}/_{x}*x*÷*2*=*x*÷*2*=^{x}/_{2}*2*÷*x*=*2*÷*x*=^{2}/_{x}*x*÷*3*=*x*÷*3*=^{x}/_{3}*3*÷*x*=*3*÷*x*=^{3}/_{x}*3x*÷*y*=*3x*÷*y*=^{3x}/_{y}*3x*÷*2y*=*3x*÷*2y*=^{3x}/_{2y}*6x*÷*4y*=*6x*÷*4y*=^{3x}/_{2y}*4x*÷*4y*=*4x*÷*4y*=^{x}/_{y}*6x*÷*3y*=*6x*÷*3y*=^{2x}/_{y}*4x*÷*2y*=*4x*÷*2y*=^{2x}/_{y}